The use of indexing languages by university libraries: systematic literature mapping - Tolare, Jessica Beatriz [UNESP] (2022)
The studies on indexing languages in university libraries are analyzed to verify similarities and differences, methods, propositions, contributions and recommendations, through the systematic mapping of literature in the databases BRAPCI, LISA, WoS and Scopus, in the period 2002-2022. The variables that can affect the indexing process are: use of controlled and inappropriate vocabulary from other areas of knowledge; attribution of indexing by the author; the professional indexer; lack of indexing policy and languages and the consonance between them; lack of method in the construction of the indexing language; unavailability of the indexing language by libraries to users; lack of an indexing manual; understanding of the professionals who perform the mediation of the indexing language and its complexity. These variables showed how the indexing process can be affected, involving aspects of the indexer, the system, the elaborated guidelines and how the indexing language construction occurs. We concluded that each study analyzed presented, at least in some aspects, similarities and differences between each other, methods, propositions, contributions and recommendations. Using only the indexing policy guidelines and the manual is not enough to solve all the problems involving the indexing process, it is necessary to perform a combination of multifactors, which are: the indexer, the quality of the indexing language in its construction, the instrument used, the systems and the context of the university library.